2022
DOI: 10.1155/2022/7741545
|View full text |Cite
|
Sign up to set email alerts
|

One in a Million: A Case Report of Stiff Person Syndrome

Abstract: Stiff person syndrome (SPS) is a rare autoimmune disease caused by lack of inhibition to excitatory neurotransmitters in the central nervous system (CNS) leading to inappropriate motor unit firing. The pathophysiology is incompletely understood; however, high titers of antiglutamic acid decarboxylase antibody (anti-GAD Ab) are strongly associated with this disease. We present a 50-year-old woman with a history of ongoing gait and balance issues for 5 years with multiple negative workups. She recently had an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Yadav et al reported a case of SPS with balance and gait abnormalities [11], whereas, Smith and Storey reported a case of SPS with acute onset vertical diplopia with subacute lower limb spasticity [12]. Dumitrascu et al [13] and Barker et al [14] reported some SPS patients presenting with urinary retention.…”
Section: Stiff-person Syndromementioning
confidence: 99%
“…Yadav et al reported a case of SPS with balance and gait abnormalities [11], whereas, Smith and Storey reported a case of SPS with acute onset vertical diplopia with subacute lower limb spasticity [12]. Dumitrascu et al [13] and Barker et al [14] reported some SPS patients presenting with urinary retention.…”
Section: Stiff-person Syndromementioning
confidence: 99%
“…Research indicates that autoimmune conditions and paraneoplastic disorders are the most prevalent causes of SPS. Considering autoimmune disease and paraneoplastic syndromes as the main causes of SPS, this reveals the importance of further investigation to determine the underlying etiology 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Considering autoimmune disease and paraneoplastic syndromes as the main causes of SPS, this reveals the importance of further investigation to determine the underlying etiology. 3,4 In this article, we report a case of an older adult who was admitted to the emergency department complaining…”
mentioning
confidence: 99%
“…Stiff Person Syndrome (SPS) is a rare autoimmune disease with an estimated prevalence of 1 -2 cases per million people [1]. It is caused by a lack of inhibition of excitatory neurotransmitters in the CNS, leading to continuous involuntary muscle excitation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Stiff Person Syndrome (SPS) is a rare autoimmune disease with an estimated prevalence of 1 -2 cases per million people [1]. It is caused by a lack of inhibition of excitatory neurotransmitters in the CNS, leading to continuous involuntary muscle excitation [1]. It has various presentations, including incomplete localized stiffness in only one limb (stiff limb syndrome, SLS) to fulminant stiff-ness with encephalomyelitis, brainstem dysfunction, and dysautonomia (progressive encephalomyelitis with rigidity and myoclonus, PERM) [2].…”
Section: Introductionmentioning
confidence: 99%